TINJAUAN PSIKOLOGIS HUMANISTIK DALAM PEDAGOGIK SPIRITUAL - Deni Irawati; Lidia Putri; Hidayani Syam (ADIBA : JOURNAL OF EDUCATION, 2024)
This article has a main focus in examining the humanistic content, the verses of the Koran which have humanist educational values, and their development in spiritual pedagogical practices. This research is in the form of a descriptive narrative with a literature study method, which shows the results of the research consisting, about Humanistic Psychological theories, Spiritual Pedagogics with studies some verses about Spiritual Pedagogics, and the last this article talk about the implications of these verse in the development of PAI learning. The obligation to recover psychological learners is very convincing for all educators without exception. Education will have a better quality, when educators carry out their duties as instructors, mentors, facilitators, and motivators, as exemplified by the Prophet Muhammad. in educating all Muslims to this day. This article implied that human have fluctuating level of faith, so it takes continuous contextual learning in every moment, and the important thing is teacher must have high optimism, if wanted spiritual of student strengthen up.